2018
DOI: 10.1167/iovs.18-24322
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Palisade Endings Only in the Medial and Inferior Rectus Muscle in Monkey Contain Calretinin

Abstract: PurposeTo further chemically characterize palisade endings in extraocular muscles in rhesus monkeys.MethodsExtraocular muscles of three rhesus monkeys were studied for expression of the calcium-binding protein calretinin (CR) in palisade endings and multiple endings. The complete innervation was visualized with antibodies against the synaptosomal-associated protein of 25 kDa and combined with immunofluorescence for CR. Six rhesus monkeys received tracer injections of choleratoxin subunit B or wheat germ agglut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 55 publications
(87 reference statements)
4
9
0
Order By: Relevance
“…Consistent with previous studies, 21 , 33 , 34 nerve fibers forming palisade endings exhibited ChAT immunoreactivity. We found palisade endings which were supplied by single axons and others by up to four axons ( Figs.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous studies, 21 , 33 , 34 nerve fibers forming palisade endings exhibited ChAT immunoreactivity. We found palisade endings which were supplied by single axons and others by up to four axons ( Figs.…”
Section: Resultssupporting
confidence: 92%
“… 10 , 11 , 21 By immunolabeling, we demonstrated that all nerve fibers forming palisade endings expressed ChAT and all terminal varicosities of palisade endings expressed ChAT as well. These findings confirmed previous studies 17 , 21 , 34 that showed that palisade endings are exclusively cholinergic.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations